Properties and Characterization of Building Materials from the Laosicheng Ruins in Southern China*. Issue 1656 (22nd August 2014) - Xiao, Ya; Wang, Ning; Gu, Haibin; Guo, Weimin; Gao, Feng; Niu, Ning; Liu, Shaojun
ABSTRACT: As one of the most typical ancient cultural relics in southern China's minority regions near Changsha in Hunan province, the magnificent Laosicheng ruins excavated recently have been included in the UNESCO World Cultural Heritage Tentative List. Urgent conservation of excavated Laosicheng ruins brings about the need for a study of the formulation and properties of construction materials used, including earth, stone, mortar, and brick. In the present study, comprehensive analyses were carried out to determine their raw material compositions, mineralogical, and microstructural properties using sheet polarized optical microscopy, scanning electron microscopy with energy dispersive spectrometer, thermogravimetric/differential scanning calorimetry, X-ray powder diffraction, and Fourier transform infrared spectroscopy. Special attention was paid to mortars, which were the most widely used in building the Laosicheng. Results show that mortar used as external render of the city wall is mainly built up from inorganic CaCO3 and MgCO3 based hybrid materials produced by the carbonation of Ca(OH)2 and Mg(OH)2 with a small amount of sticky rice. In contrast, mortar used to bond stones of the city walls is a traditional mortar that does not contain sticky rice. This study is a part of a huge interdisciplinary project aimed to clarify the role of organics in ancient China's organic-inorganic hybrid mortar, which can be considered as one of the greatest invention in construction material history. The results provide valuable basic data and restoration strategies that can be used in the conservation of the ruins as well.